Characterization of Foundational Literacy Instruction for Early Grade Students Based on Their Skill Levels - Syarifudin Syarifudin; Nurrahmah; Sholihin; Ria Widiyanti (Jurnal Pendidikan Matematika (JPM), 2024)
This research aims to describe the characteristics of basic literacy learning among early grade students based on their skill levels or through Teaching at the Right Level (TaRL) approach. The research subjects consist of 15 third-grade students from Rompo Elementary School. The research instruments include initial diagnostic tests and progress tests conducted during the learning process. The research findings indicate that the first level group's approach involves introducing children to the smallest components of literacy skills, namely sounds and letters, as well as distinguishing various phonetic variations of these letters. In Group B, students enhance their reading fluency through regular reading exercises, building text comprehension skills, and starting to understand unusual combinations of letters and pronunciations. Group C engages in collaborative reading within small groups, answering a series of questions about the text, drawing conclusions about the meanings of foreign words, and transitioning from simple to complex conceptual understanding. Students are encouraged to practice writing daily, read together, and evaluate each other's work to strengthen their abilities in identifying spelling errors, grammar, and common punctuation.